2009
DOI: 10.1038/sj.bjc.6604927
|View full text |Cite
|
Sign up to set email alerts
|

Apollon gene silencing induces apoptosis in breast cancer cells through p53 stabilisation and caspase-3 activation

Abstract: We analysed the effects of small interfering RNA (siRNA)-mediated silencing of Apollon, a member of the inhibitors of apoptosis protein family, on the proliferative potential and ability of human breast cancer cell lines to undergo apoptosis. In wild-type p53 ZR75.1 cells, Apollon knockdown resulted in a marked, time-dependent decline of cell growth and an increased rate of apoptosis, which was associated with p53 stabilisation and activation of the mitochondrial-dependent apoptotic pathway. Pre-incubation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
58
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 19 publications
4
58
2
Order By: Relevance
“…To our knowledge, these are the first data to demonstrate the PD-induced alterations in p53 expression in gastrocnemius muscle. P53 has been reported to induce apoptosis by caspase activation eventually leading to the cleavage and the subsequent activation of caspase-3 (Lopergolo et al, 2009;Nigam et al, 2009;Pratheeshkumar et al, 2010;Chan et al, 2010;Son et al, 2010;Choi et al, 2010;Pratheeshkumar et al, 2012). Thus, to further investigate the occurrence of apoptosis in gastrocnemius muscle, we tested the alterations in active caspase-3 expression following the induction of PD.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, these are the first data to demonstrate the PD-induced alterations in p53 expression in gastrocnemius muscle. P53 has been reported to induce apoptosis by caspase activation eventually leading to the cleavage and the subsequent activation of caspase-3 (Lopergolo et al, 2009;Nigam et al, 2009;Pratheeshkumar et al, 2010;Chan et al, 2010;Son et al, 2010;Choi et al, 2010;Pratheeshkumar et al, 2012). Thus, to further investigate the occurrence of apoptosis in gastrocnemius muscle, we tested the alterations in active caspase-3 expression following the induction of PD.…”
Section: Discussionmentioning
confidence: 99%
“…Given that p53, a critical molecular in regulating tumor proliferation and apoptosis, is closely related to IAPs. 10,11 We determined the p53 expression in these cells. It is evident that BIRC6 knockdown significantly increased the protein levels of endogenous p53, but did not change the mRNA levels of endogenous p53 (Figs.…”
Section: Birc6 Interacted With P53 and Facilitated Its Degradation Bymentioning
confidence: 99%
“…9 Notably, previous studies have found that p53 is a key downstream effector of BIRC6. 10,11 However, it is unclear whether BIRC6 can interact with p53, and in which way BIRC6 regulates p53. Meanwhile, the role of such association in HCC carcinogenesis remains unknown.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The regulation of Bruce protein expression plays an important role in apoptosis, as an increase or decrease in this protein expression changes the cell susceptibility to a death stimulus. Thus, understanding BIRC6 gene expression is perceived as being a new therapeutic aim in the treatment of malignancies characterized by its over-expression [24,17].…”
Section: Resultsmentioning
confidence: 99%